2015
DOI: 10.1039/c4sm02787f
|View full text |Cite|
|
Sign up to set email alerts
|

Design of a robust superhydrophobic surface: thermodynamic and kinetic analysis

Abstract: The design of a robust superhydrophobic surface is a widely pursued topic. While many investigations are limited to applications with high impact velocities (for raindrops of the order of a few m/s), the essence of robustness is yet to be analyzed for applications involving quasi-static liquid transfer. To achieve robustness with high impact velocities, the surface parameters (geometrical details, chemistry) have to be selected from a narrow range of permissible values, which often entail additional manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…For example, some species are able to resist droplet impacts during rainfalls, to slide easily on aquatic surfaces or to see clearly in foggy environments . It was shown that the presence of both micro and nanostructures and low surface energy materials can lead to “robust” superhydrophobic properties . However, it is also extremely important to repel low surface tension liquids such as oils, which is much more difficult due to their high tendency to spread across any substrate .…”
Section: Introductionmentioning
confidence: 99%
“…For example, some species are able to resist droplet impacts during rainfalls, to slide easily on aquatic surfaces or to see clearly in foggy environments . It was shown that the presence of both micro and nanostructures and low surface energy materials can lead to “robust” superhydrophobic properties . However, it is also extremely important to repel low surface tension liquids such as oils, which is much more difficult due to their high tendency to spread across any substrate .…”
Section: Introductionmentioning
confidence: 99%
“…The first type of wetting transition corresponds to the crossing of a critical pressure difference, driven by the dynamic pressure inside water drops. This type of failure occurs by destabilizing the triple-phase contact line (contact line where air, liquid, and solid converge) and subsequent penetration of the liquid-air interface into surface pores [23,24]. The second type of wetting transition can occur even when the contact line remains pinned to the top of the surface texture: any pressure differential across the liquid-air interface leads to the sagging of the interface, and if the bulging interface can touch the bottom of the texture, such a local wetting can quickly spread across the entire surface [20,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…This type of failure occurs by destabilizing the triple-phase contact line (contact line where air, liquid, and solid converge) and subsequent penetration of the liquid-air interface into surface pores [23,24]. The second type of wetting transition can occur even when the contact line remains pinned to the top of the surface texture: any pressure differential across the liquid-air interface leads to the sagging of the interface, and if the bulging interface can touch the bottom of the texture, such a local wetting can quickly spread across the entire surface [20,23,25]. In both cases, the driving force for the transition is pressure, which, for the case of dynamic impact, originates from the transfer of momentum of the drop [18,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main parameters influencing both the surface hydrophobicity and water adhesion are the surface chemistry and the topography of the surface roughness. Usually, low surface energy materials and dual‐scale or hierarchical surface roughness are used to obtain stable superhydrophobic properties with low adhesion but the adhesion can be increased by using materials of higher surface energy and/or by creating one‐scale surface roughness (e.g., nanofibers) …”
Section: Introductionmentioning
confidence: 99%